Psychological processes underlying the association between childhood trauma and psychosis in daily life: an experience sampling study. Issue 13 (12th July 2016) - Reininghaus, U.; Gayer-Anderson, C.; Valmaggia, L.; Kempton, M. J.; Calem, M.; Onyejiaka, A.; Hubbard, K.; Dazzan, P.; Beards, S.; Fisher, H. L.; Mills, J. G.; McGuire, P.; et al.
Abstract : Background: Evidence has accumulated that implicates childhood trauma in the aetiology of psychosis, but our understanding of the putative psychological processes and mechanisms through which childhood trauma impacts on individuals and contributes to the development of psychosis remains limited. We aimed to investigate whether stress sensitivity and threat anticipation underlie the association between childhood abuse and psychosis. Method: We used the Experience Sampling Method to measure stress, threat anticipation, negative affect, and psychotic experiences in 50 first-episode psychosis (FEP) patients, 44 At-Risk Mental State (ARMS) participants, and 52 controls. Childhood abuse was assessed using the Childhood Trauma Questionnaire. Results: Associations of minor socio-environmental stress in daily life with negative affect and psychotic experiences were modified by sexual abuse and group (all p FWE < 0.05). While there was strong evidence that these associations were greater in FEP exposed to high levels of sexual abuse, and some evidence of greater associations in ARMS exposed to high levels of sexual abuse, controls exposed to high levels of sexual abuse were more resilient and reported less intense negative emotional reactions to socio-environmental stress. A similar pattern was evident for threat anticipation. Conclusions: Elevated sensitivity and lack of resilience to socio-environmental stress and enhanced threat anticipation in daily life may be important psychological processes underlying the association between childhood sexual abuse and psychosis.